Pengembangan Media Gamifikasi Berbasis Aplikasi Kahoot pada Materi Perkalian untuk Siswa Kelas II pada Mata Pelajaran Matematika di Sekolah Dasar Islam Terpadu Al-Azhar Galang Kota - Adelia Amanda; Astria Ayu Ramadianti; Emy Hariati (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2025)
This study develops and evaluates a gamification-based learning media using the Kahoot application to enhance second-grade students’ understanding of multiplication at the Integrated Islamic Elementary School Al-Azhar Galang. The research addresses the problem of low student engagement and limited variation in instructional media by proposing a digital game-based alternative designed to increase motivation and conceptual mastery. Employing a Research and Development design with the ADDIE model, the study involved material experts, media experts, and Grade II students as trial participants. Data were collected through expert validation questionnaires and classroom implementation observations, and analyzed descriptively using quantitative techniques. Findings indicate that the developed media demonstrates high feasibility, receiving validation scores of 86% from both material and media experts, categorized as highly feasible. Student trial results yielded an average score of 90.8%, showing that the media is interactive, enjoyable, and effective in supporting students’ understanding of multiplication. The Kahoot-based learning media incorporates structured sections—introduction, core activities, and closing—supported by age-appropriate illustrations and game elements that align with the principles of gamified learning. Overall, the study concludes that the developed media is suitable for classroom use and contributes positively to students’ learning motivation and conceptual comprehension.